A shear strength criterion for the buckling analysis of CLT walls. (15th May 2020) - Perret, Olivier; Douthe, Cyril; Lebée, Arthur; Sab, Karam
Highlights: Adapted strength criterion for buckling of CLT walls considered as shear weak members. New strength criterion for buckling of CLT walls including rolling shear effects. Extension of the preceding shear strength criterion to long term behaviour. Study of the relevance of the new criterion on three practical configurations. Abstract: The proper sizing of Cross Laminated Timber (CLT) walls for the construction of high rise buildings requires to take into account their low shear stiffness and their viscoelastic properties and to integrate them into the framework of actual building codes which are all based upon Ayrton-Perry approach of imperfect columns. The present paper starts thus by recalling the framework of Linear Buckling Analysis of shear weak columns using the Timoshenko beam model. Then, Ayrton-Perry approach of the buckling of imperfect columns is introduced and used to develop a normal stress strength criterion for CLT walls but also an additional shear strength criterion. Both criteria are compared for three characteristic sizes of initial imperfections. Afterwards, orthotropic creep is introduced and its effect on long term stability of shear weak members is investigated and an extension of the previous criteria to long term behaviour is developed. Throughout the study, three numerical examples are used for illustration (a low strength panel, a high strength and an aerated panel) revealing the importance of proposed shear strength verification and the need of experimental characterisation.